Evaluation of a flat sheet woven fabric membrane for use in water treatment processes suited to rural and peri-urban economies - Asquith, Joshua Steven (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.